Mathematical modeling with Excel - Albright, Brian, 1977-; Fox, William P., 1949- (Boca Raton, FL : CRC Press, 2020)
This text presents a wide variety of common types of models found in other mathematical modeling texts, as well as some new types. However, the models are presented in a very unique format. A typical section begins with a general description of the scenario being modeled. The model is then built using the appropriate mathematical tools. Then it is implemented and analyzed in Excel via step-by-step instructions. In the exercises, we ask students to modify or refine the existing model, analyze it further, or adapt it to similar scenarios.
OCLC-licensed vendor bibliographic record.
Keywords: Electronic spreadsheets -- Data processing; BUSINESS & ECONOMICS / Operations Research; MATHEMATICS / General; MATHEMATICS / Applied